Implementasi Manajemen Sumber Daya Manusia Ramah Lingkungan - Hardianti, Hardianti; Otoluwa, Narto Irawan; Amri, Andi; Swandani, Swandani (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2025)
This research aims to measure the implementation of environmentally friendly human resource management. The role of environmentally friendly human resource management in sustainable performance which includes environmentally friendly lighting which currently does not use physical documents in this process, work management and completion in the process has minimized the use of paper because in the current era digitalization is used. , as well as in the training process in research. The research method used is this research uses qualitative descriptive research. This research design was carried out by collecting secondary data to review several journals and publications related to the objectives of this research. The research results show the success of an organization in implementing environmentally friendly human resource management based on Riveuw literature which can be implemented with a Green Recruitment and Selection program, apart from that there is Green Training and Development as well as a Green Performance Management program and finally the Green Reward and Compensation program..